Resonance based fault location for DC photovoltaic integration system. (July 2021) - Jia, Ke; Shi, Zhiming; Chen, Cong; Chen, Miao; Bi, Tianshu
Highlights: It is demonstrated that the high-frequency fault component circuit is immune to the states of the converter switches. The relationship between the fault distance and resonance current is derived by analyzing the faulted high frequency network. The proposed method does not require a high sampling frequency and additional injection source. The proposed method can perform well when considering the distributed capacitance, fault resistance, and measurement noise. Abstract: Photovoltaic (PV) power DC integration systems can be applied in remote areas in which conventional AC cable integration is inhibited by PV collection and transmission distance. However, unpredictable DC fault transients create challenges for traditional fault location methods. To address this issue, a high-frequency resonance estimation based fault location technique is proposed in this paper. Series resonance is generated by discharging the DC capacitor through a current-limiting reactor, which weakens the attenuation of high-frequency signals at the line boundary. The relationship between resonance current and fault distance can then be obtained by analyzing the fault current loop, which is immune to the states of the converter. Compared with the traditional fault location method, the proposed method does not require additional high-frequency injection sources and very high sampling frequency. A flexible DC photovoltaic integration system is also built in PSCAD/EMTDC and the simulation results verify the accuracy of the proposed location method.